The 'national past' in the training of History teachers in the province of Buenos Aires. An approach from Curriculum Design (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
In this article, we analyze the new study plan of the History Teachers of the province of Buenos Aires (effective as of 2022). On the one hand, we wonder about the articulation and dialogue that the new curricula maintains with the renewed theoretical and historiographic perspectives present in the secondary’s Curricular Designs and, on the other, what is the treatment and place that some themes or topics occupy in teacher training. Contents that appear traditionally linked to the “national past” and, for a long time, were central in the identity and citizen definition that the educational system pursued. In addition, in order to enrich the approach of the new curricular document, we draw some comparisons between it and the old Curricular Design (1999) for the training of teachers in History.
Keywords: teacher training; History; nation; nationalism; curriculum design